Ethnic specific differences in survival of patients with type 2 diabetes: Analysis of data collected from an Australian multi-ethnic cohort over a 25 year period. Issue 1 (January 2015) - Alharbi, Turki J.; Constantino, Maria I.; Molyneaux, Lynda; Wu, Ted; Twigg, Stephen M.; Yue, Dennis K.; Wong, Jencia
Highlights This is a study of the diabetes complications and mortality of 7 ethnic groups that lived in the same environment in Australia and sharing equal access to health care. The Chinese patients seemed to have lower mortality while the Indigenous Australians had higher mortality, even after adjustment for risk factors. The survival of the Anglo-Celtic patients was poorer than many other ethnic groups. The lack of acculturation, as judged by a poorer ability to communicate in English, had a favourable impact on survival, suggesting that westernization of lifestyle may be detrimental.